2021
DOI: 10.3390/nu13062097
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of COVID-19-Related Perceived Improvements in Dietary Health: Results from a US Cross-Sectional Study

Abstract: The COVID-19 pandemic resulted in substantial lifestyle changes. No US study has identified predictors of perceived dietary healthfulness changes during the pandemic period. This study included analyses of lifestyle and dietary healthfulness changes using 958 survey responses from US primary household food purchasers. Information was collected related to demographics, COVID-19-related household changes, and health-related habits before and during the pandemic. Binary logistic regression identified predictors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…Górnicka et al (2020) also found similar results among Polish adults, who showed increased food consumption and snacking during restrictive measures, especially among those with higher BMI [ 3 ]. Similar results were noticed by Cosgrove and Wharton (2021), who found that participants most often reported purchasing more food in various food categories [ 36 ]. In France, the nutritional quality of the diet was also higher before the lockdown than during the pandemic [ 10 ].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Górnicka et al (2020) also found similar results among Polish adults, who showed increased food consumption and snacking during restrictive measures, especially among those with higher BMI [ 3 ]. Similar results were noticed by Cosgrove and Wharton (2021), who found that participants most often reported purchasing more food in various food categories [ 36 ]. In France, the nutritional quality of the diet was also higher before the lockdown than during the pandemic [ 10 ].…”
Section: Discussionsupporting
confidence: 87%
“…Food insecurity is inversely associated with diet quality [ 36 ]. A recent study showed that females, with lower education and incomes, have higher overweight and obesity levels in Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations